Late Victorian orientalism : representations of the east in nineteenth-century literature, art and culture from the pre-Raphaelites to John la Farge /: representations of the east in nineteenth-century literature, art and culture from the pre-Raphaelites to John la Farge. (2020) - Unknown
No abstract available